Cancers in Australia in 2010 attributable to total breastfeeding durations of 12 months or less by parous women - Susan J. Jordan; Louise F. Wilson; Christina M. Nagle; Adele C. Green; Catherine M. Olsen; Christopher J. Bain; Nirmala Pandeya; David C. Whiteman; Penelope M. Webb (Elsevier, 2015)
Abstract Objectives: To estimate the proportion and number of cancers occurring in Australia in 2010 attributable to parous women having breastfed for total durations of ≤12 months. Methods: We estimated the population attributable fraction (PAF) of breast cancers (the only cancer site with convincing evidence of causal association) associated with women breastfeeding for ≤12 months in total, using standard formulae incorporating breastfeeding prevalence data, relative risks associated with breastfeeding and cancer incidence. We also estimated the proportion change in disease incidence (potential impact fraction [PIF]) that might have occurred under two hypothetical scenarios of women breastfeeding for longer durations. Results: An estimated 235 (1.7%) breast cancer cases that occurred in Australian in 2010 could be attributed to women breastfeeding for total durations of ≤12 months. Assuming a hypothetical increase in breastfeeding, we estimated that the number of breast cancers prevented would range from 36 to 51 (prevented fraction = 0.3% to 0.4%). Conclusions: More than 200 breast cancers were attributable to women breastfeeding for total durations of ≤12 months. Implications: Policies to increase breastfeeding duration may help prevent breast cancers in the future.